MiR-204/ZEB2 axis functions as key mediator for MALAT1-induced epithelial–mesenchymal transition in breast cancer. Issue 7 (July 2017) - Wang, Yuzhou; Zhou, Yijin; Yang, Zhicheng; Chen, Baoying; Huang, Wennan; Liu, Yongyuan; Zhang, Ying
Long non-coding RNAs recently were identified as key mediators of cancer metastasis. This study provided evidence that long non-coding RNA MALAT1 was up-regulated in breast cancer tissues and cell lines. MALAT1 promoted cancer cell invasion through inducing epithelial–mesenchymal transition. Interestingly, we revealed there was a reciprocal repression between MALAT1 and miR-204. ZEB2 was identified as a downstream target of miR-204 and MALAT1 exerted its function mainly through the miR-204/ZEB2 axis. Our findings suggested that MALAT1 may serve as a new diagnostic biomarker and therapy target for breast cancer.